Effect of Supplementation of Onion Peel Powder as a Herbal Feed Additive on Carcass Traits, Sensory Evaluation and Cost Economics of Japanese Quails - Mujeebulla, S. Md.; Susmita, T.; Tirupathi, Reddy E.; Raja, Kishore K. (International Journal of Bio-resource and Stress Management, 2025)
The present study was carried out during November to December, 2023 at poultry unit, livestock farm complex, NTR College of Veterinary Science, Andhra Pradesh, to evaluate the effect of supplementation of onion peel powder (OPP) as an herbal feed additive on the performance of Japanese quail. 225 day-old Japanese quails were distributed randomly into five treatments with three replicates containing fifteen birds each and were fed with five experimental diets T1 (Basal diet), T2 (Basal diet+10 g kg-1 OPP), T3 (Basal diet+20 g kg-1 OPP), T4 (Basal diet+30 g kg-1 OPP) and T5 (Basal diet+40 g kg-1 OPP) from day old to five weeks of age and were maintained under uniform management conditions. Two birds per replicate were slaughtered at the end of 5th week. The study showed that the carcass traits like pre-slaughter live weight, heart weight, and carcass weight significantly increased (p<0.01) with increasing levels of OPP. The study found that supplementing OPP in diets from 0 to 40 g kg-1 did not affect dressing percentage, liver, gizzard, giblet weights and sensory evaluation compared to other treatment groups. Quail fed with 40 g kg-1 OPP had significantly lower feed cost kg-1 gain. The study indicates that OPP can be safely supplemented up to 40 g kg-1 in the diet without any negative impact on the performance of Japanese quail.